Let's denote the unknown number as \( x \).
According to the problem, the equation can be set up as follows:
- Four times the sum of the number and four: \( 4(x + 4) \)
- Two multiplied by two less than three times the number: \( 2(3x - 2) \)
Now, we can write the equation:
\[ 4(x + 4) = 2(3x - 2) \]
Next, we can simplify both sides of the equation.
Starting with the left side:
\[ 4(x + 4) = 4x + 16 \]
Now simplifying the right side:
\[ 2(3x - 2) = 6x - 4 \]
So the equation becomes:
\[ 4x + 16 = 6x - 4 \]
Next, we will solve for \( x \). First, we can subtract \( 4x \) from both sides:
\[ 16 = 2x - 4 \]
Now add \( 4 \) to both sides:
\[ 20 = 2x \]
Finally, divide by \( 2 \):
\[ x = 10 \]
Thus, the number is \( \boxed{10} \).
To verify, we can substitute \( x = 10 \) back into the original conditions:
- Left side: \( 4(10 + 4) = 4 \times 14 = 56 \)
- Right side: \( 2(3 \times 10 - 2) = 2(30 - 2) = 2 \times 28 = 56 \)
Both sides are equal, confirming that \( x = 10 \) is indeed the correct solution.